THE EFFECT OF LENGTH OF SERVICE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE OIL PALM PLANTATION OF PT PERKEBUNAN NUSANTARA IV (CASE STUDY OF THE ADOLINA PLANTATION OF PTPN IV PANTAI CERMIN AND PERBAUNGAN DISTRICTS OF SERDANG BEDAGAI REGENCY) - Haidar Alwi Yahya. S; Yusniar Lubis; Sri Ariani Safitri (Journal of Agri Socio Economics and Business, 2023)
This Research was conducted with the aim to analyze the effect of length of working and job satisfaction on the performance of employees in the Adolina Plantation of PT Perkebunan Nusantara IV, located in the sub-district of Pantai Cermin and Perbaungan, regency of Serdang Bedagai. The used method in this research is quantitative data analysis. The sample used in this study amounted to 63 respondents. Data were collected through the use of questionnaires and observations. The analysis techniques applied include multiple linear regression, t-tests, and F-tests. Results of the study showed that the length of work does not have a significant influence on employee performance in the Adolina Garden of PT Perkebunan Nusantara IV. However, job satisfactions positively and significantly affect employee performance in the company. In addition, there is a simultaneous significant influence between length of work and job satisfaction on employee performance.